A Bioprotection Strategy of Musts to Limit Sulfiting Process During Winemaking - Sabin Ioan BANIȚĂ; Anca Cristina BABEȘ; Florin-Dumitru BORA; Dorin Ștefan DUȘA; Anamaria CĂLUGĂR; Andrea BUNEA; Claudiu Ioan BUNEA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2024)
In the wine industry, sulfur dioxide (SO2) has an important role, as an antioxidant, and antiseptic additive. Lately, manufacturers of products specific to wine production technology are developing biological protocols for treating musts and wines using different types of yeasts. The purpose of the research is to study the impact of replacing SO2 in the first phase of the winemaking process with biological methods on the flavonoids, polyphenols, and antioxidant potential in Fetească neagră wine. The red wine from Fetească neagră, 2021 harvest - Dealu Mare Vineyard was made through two methods: treated with SO2 6% (25 mg/L) and treated with Primaflora VR Bio (7 g/hL). The IC50 value for the variant treated with Primaflora VR BIO was 722 mg/mL and the variant treated with SO2 recorded a 724 mg/ml, the differences being non-significant. Primaflora VR Bio is an effective and promising alternative in terms of the quality of oenological and biochemical parameters, and a basic variant for ecological, biological wines with a low sulfite content.